Theoretical background of light‐emitting diode total internal reflection fluorescence microscopy and photobleaching lifetime analysis of membrane‐associated proteins—Part II. Issue 4 (5th February 2020) - Schaefer, Michael; Kalwa, Hermann
Abstract: The selective microscopic imaging of the plasma membrane and adjacent structures by total internal reflection fluorescence (TIRF) microscopy is a versatile and frequently used technique in cell biology. A reduction of imaging artifacts in objective‐type TIRF microscopy can be achieved by circular or multi‐spot laser illumination or by using noncoherent light sources that are projected into the back focal plane as a light annulus. Light‐emitting diode (LED)‐based TIRF excitation is a recent advancement of the latter strategy. While some basic principles of LED‐TIRF remain the same as in laser‐based methods, the calculation of penetration depth, the flatness of illumination and the amount of available illumination power differ. This study provides the theoretical framework for the construction and adjustment of LED‐TIRF. Using state‐of‐the art high power LED emitters, LED‐TIRF achieves excitation efficiencies that are comparable to laser‐based systems and homogenously illuminate the entire field of view, thus, allowing variation of the penetration depth or quantitative photobleaching‐assisted imaging protocols. Using autofluorescent transmembrane, soluble and membrane‐attached fusion proteins, we provide examples for a photobleaching‐based assessment of the exchange kinetics of proteins within living human endothelial cells. Abstract : We provide a novel spin on the use of light‐emitting diode (LED) illumination for artifact‐free total internal reflection fluorescence (TIRF) microscopy, describing the theoretical background and application of a solid state TIRF, constructed with inexpensive off‐the‐shelf parts. The power density in LED‐TIRF is comparable with conventional laser systems in combination with uniform illumination of the visual field. The suitability of LED‐TIRF for demanding applications is confirmed by measuring the susceptibility to photobleaching in living cells.